2020
DOI: 10.1101/2020.07.30.229492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network variants are similar between task and rest states

Abstract: Recent work has demonstrated that individual-specific variations in functional networks can be reliably identified in individuals using functional magnetic resonance imaging (fMRI). These individual differences in functional connectivity have been termed network variants and exhibit reliability across time with resting-state fMRI data. These properties have suggested that network variants may be relatively trait-like markers of individual differences in brain organization. Another test of this conclusion would… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…the two large communities discussed in the previous section. These observations align with other studies showing that the individualization of FC is generally a subtle modulation of features that are evident in group-level data, from brain systems [46][47][48] to regional FC fingerprints [8].…”
Section: High-amplitude Cofluctuation Patterns Are Individualized Andsupporting
confidence: 91%
“…the two large communities discussed in the previous section. These observations align with other studies showing that the individualization of FC is generally a subtle modulation of features that are evident in group-level data, from brain systems [46][47][48] to regional FC fingerprints [8].…”
Section: High-amplitude Cofluctuation Patterns Are Individualized Andsupporting
confidence: 91%
“…Lastly, the spatial resolution of the current data is lower than used in the state-of-the-art studies (Glasser, Smith, et al, 2016; K. L. Miller et al, 2016). However, it is still representative of the numerous sets of legacy data (Kraus et al, 2020; Teipel et al, 2017), with an important advantage of critically sampling cardiac and respiratory noise peaks. This latter allows us a unique advantage to decipher the effects of low-frequency artifacts, although this results in the use of a lower than usual flip-angle (40 degrees).…”
Section: Discussionmentioning
confidence: 99%
“…Patients underwent presurgical fMRI for language localization. Previous studies have shown that the intraindividual effect of any task or state on network topology is small in comparison to interindividual differences in network topology (Gratton et al 2018;Kraus et al 2021), indicating that we may use these pseudo resting-state data to investigate individual differences in network integration. Resting-state analysis has previously been used on such task data for network analysis in both healthy controls and patients (Harris et al 2014;Krienen et al 2014;Derks et al 2017).…”
Section: Functional Magnetic Resonance Imagingmentioning
confidence: 99%